Reviewing two decades of energy system analysis with bibliometrics. (January 2022) - Dominković, D.F.; Weinand, J.M.; Scheller, F.; D'Andrea, M.; McKenna, R.
Abstract: The field of Energy System Analysis (ESA) has experienced exponential growth in the number of publications in the last two decades. This paper presents a comprehensive bibliometric analysis on ESA by employing different statistical techniques to investigate the underlying science's structure, characteristics, and patterns. The focus of results is on quantitative indicators relating to the number and type of publication outputs, collaboration links between institutions, authors and countries, and dynamic trends within the field. The five and twelve most productive countries have 50% and 80% of ESA publications, respectively. The dominant institutions are even more concentrated within a small number of countries. A significant concentration of published papers within countries and institutions was also confirmed by analysing collaboration networks. These show dominant collaboration within the same university or at least the same country. There is also a strong link among the most successful journals, authors and institutions. Within the field, the Energy journal has had the most publications, its editor-in-chief is the author with both the highest overall number of publications and the most highly cited publications. In terms of the dynamics within the field in the past decade, recent years have seen a higher impact of topics related to flexibility and hybrid/integrated energy systems alongside a decline in individual technologies. This paper provides a holistic overview of two decades' research output and enables interested readers to obtain a comprehensive overview of the key trends in this active field. Highlights: A review of more than 12, 000 papers in the field of Energy System Analysis (ESA). Five countries with 50% of publications: USA, China, UK, Germany, Italy. Strong link among the most successful journals, authors and institutions. Collaboration networks predominantly include only institutions within the same country. Strong Nordic influence related to region's energy culture and policy.